From Quality to Clicks: Analyzing the Influence of Service, Promotion, and Product Quality on Shopee Consumers Purchasing Decisions Toward Rabbani Muslim Fashion - Asytuti, Rinda; Aniroh; Devy, Happy Sista (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Indonesia, with its Muslim-majority population, has witnessed rapid growth in the Muslim fashion industry. According to the National Committee for Islamic Economics and Finance (KNEKS), Indonesia aims to be the world’s halal producer. The expansion of the halal industry in several fields, including the Muslim fashion industry, is necessary. This study aims to analyze the influence of service quality, promotion, and product quality on the purchasing decisions of Rabbani products via Shopee. Purpose: This study aimed to determine the effects of service quality, promotion, and product quality on purchasing decisions for Rabbani products through Shopee e-commerce. Design/Methodology/Approach: This research was conducted in the Sidorejo-comal Village environment, and data were obtained from 74 respondents who use the Shopee application, especially women. The number of respondents helps researchers in quantitative research conducted to determine developments in the Shopee application. Data analysis used validity, reliability, normality, and hypothesis tests.Findings/Results: The results of this study are based on the t-test, which obtained 1.994. The variables that have a significant effect on purchasing decisions are promotion with tcount (5.043) and product quality with tcount (3.206). The variable that does not have a significant effect on purchasing decisions is service quality with a tcount value (-0.423). The F test shows that simultaneously, the three variables have a significant effect on purchasing decisions with fcount (12.569) > ftable (2.74).Conclusion: Based on the research findings, it can be concluded that purchasing decisions for Rabbani Muslim clothing through the Shopee platform in Sidorejo Village, Comal District, are more strongly influenced by promotion and product quality than by service quality. Although service quality does not show a significant effect when examined individually, it contributes significantly when combined with promotion and product quality. This indicates that marketing strategies focusing on improving product quality and effective promotional activities, supported by adequate service quality, are essential in encouraging consumers’ purchasing decisions.Keywords:  service quality, promotion, product quality, purchase decision, muslim clothing